Indwelling pleural catheters for pleural effusions associated with end-stage renal disease: a case series. (February 2015) - Potechin, Rajini; Amjadi, Kayvan; Srour, Nadim
Background: Pleural effusions are a common complication of end-stage renal disease. These effusions are occasionally refractory to medical management, but few options are then available. Indwelling pleural catheter insertion (IPC) has been well described for the management of malignant pleural effusions and, more recently, of nonmalignant effusions of other origin. We aimed to analyze our experience and to evaluate the safety and feasibility of using IPCs for pleural effusion associated with end-stage renal disease. Methods: We constructed a cohort of patients who underwent IPC insertion for pleural effusions associated with end-stage renal disease. The IPCs were inserted as a palliative measure in patients who had thoracentesis twice within the preceding 2 weeks, no evidence of infection and either failure to respond, complications or intolerance to maximal medical therapy, or if IPC insertion would enable discharge when the patient was hospitalized mainly for dyspnea due to pleural effusion. Results: There were nine IPCs inserted in eight patients. Patients had significant dyspnea at baseline with a median baseline dyspnea index of 1.5 [interquartile range (IQR) 0–3]. Dyspnea improved significantly 2 weeks after catheter insertion with a median transitional dyspnea index of 6 (IQR 4.5–7.0). There was no occurrence of empyema or other major complications. Serum albumin did not decrease after catheter insertion. IPCs were removed in four patients (50%) and successful spontaneous pleurodesis occurred in three patients (37.5%) after a median of 77 days (IQR 9–208). Conclusion: IPC insertion for pleural effusions associated with end-stage renal disease appears safe and effective. Larger studies are needed, particularly regarding the impact of this intervention on quality of life.